Mental health law in Montenegro - Lidija Injac Stevovic; Tatijana Perunovic Jovanovic; Aleksandra Raznatovic (BJPsych International, 2016)
This paper discusses the services and treatments that are offered in Montenegro to persons who are mentally ill. A short history is given. The law on the protection of the rights of patients who are mentally ill is described, along with the regulations governing voluntary and forced treatment. An action plan for promoting mental health has been partly already realised but some of its aims still need to be accomplished.